3D virtual reality simulation in radiography education: The students' experience. Issue 1 (February 2021) - O'Connor, M.; Stowe, J.; Potocnik, J.; Giannotti, N.; Murphy, S.; Rainford, L.
Abstract: Introduction: Simulation forms a key element of undergraduate Radiography education as it enables students to develop their clinical skills in a safe environment. In this study, an immersive three-dimensional (3D) virtual radiography simulation tool was piloted in an undergraduate Radiography curriculum and user feedback retrieved. Methods: The 3D virtual simulation tool by Virtual Medical Coaching Ltd was introduced to first year radiography students (n = 105). This technology guided students through a comprehensive process of learning anatomy, radiographic positioning and pathology. Students then X-rayed a virtual patient in the VR suite using HTC Vive Pro™ headsets and hand controllers. Instant feedback was provided. An online survey was later disseminated to students to gather user feedback. Thematic and descriptive statistical analyses were applied. Results: A response rate of 79% (n = 83) was achieved. Most respondents (58%) reported enjoying VR simulation, whilst some felt indifferent towards it (27%). Ninety-four percent would recommend this tool to other students. The mean length of time it took for students to feel comfortable using the technology was 60 min (10–240 min). Most respondents (58%) desired more VR access. Students attributed enhanced confidence in the areas of beam collimation (75%), anatomical marker placement (63%), centring of the X-ray tube (64%) and exposure parameter selection (56%) to their VR practice. Many students (55%) advocated the use of VR in formative or low stakes assessments. Issues flagged included technical glitches, inability to palpate patient and lack of constructive feedback. Conclusion: Student feedback indicates that 3D virtual radiography simulation is a valuable pedagogical tool in radiography education Implications for practice: 3D immersive VR simulation is perceived by radiography students to be a valuable learning resource. VR needs to be strategically implemented into curricula to maximise its benefits.